Analisis Penerapan Metode Algoritma Apriori Untuk Melihat Minat Pengunjung Pada Objek Wisata Kota Palembang - Astri Cahaya Plangi; Tri Basuki Kurniawan (Jurnal Ilmiah Matrik, 2020)
The management of tourist destinations in Palembang City is managed by the Dinas Pariwisata, Tourism in Palembang City is classified into 3 Tourism, namely Nature Tourism, Cultural History Tourism, and Special Interests. However, Dinas Pariwisata has not seen the pattern of interest of visitors from grouped tours. This makes the authors want to determine the patterns of interest of the respondents by distributing questionnaires to 100 respondent. The results show that there are 10 rules established by the WEKA application with a minimum support value of 5% and a minimum confidence value of 50%. The results of the pattern formed are Al-Qur'an Al-akbar, Musi River, and Ampera Bridge with a confidence value of 90%.